ENGLISH TRANSLATIONAL EQUIVALENTS OF THE MACEDONIAN POTENTIAL MOOD WITH PRAGMATIC FUNCTION (Journal of Contemporary Philology, 2019)
This paper presents the  results of the  investigation of the  English equivalents of the bi-construction used in pragmatic functions.  The bi-construction in Macedonian is the main  marker  of  the  potential  mood  encoding  hypotheticality  and  volition.  Unlike English,  which  employs  modal  verbs  to  render  these  meanings,  the bi-construction recruits both modal and lexical verbs in its structure. In non-conditional uses,potential mood  forms  may  perform  a  range  of  pragmatic  functions  related  to  politenessand hedging. The goal of the investigation is to determine whether the pragmatic functiontends to be performed by bi-constructions based on modal or lexical verbsand whether this influences the choice of the translational equivalent in English. The results show that potential mood bi-constructions containing a modal verb are more frequent. The analysis confirmed the hypothesis that pragmatically used bi-constructions tend to be translated with the modal verb would. Moreover, there seems to exist a strongsemantic correlation  between  the bi-construction  based  on  a  particular  modal  verb  and  its English equivalent: thus saka chooses would, može–could, and treba–should.
Keywords: modality; potential mood; modal verbs; pragmatic function; politeness